先化简,再求值:(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),其中a=2002/2003,b=2003/2002

来源:学生作业帮助网 编辑:作业帮 时间:2022/05/23 07:45:08
先化简,再求值:(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),其中a=2002/2003,b=2003/2002

先化简,再求值:(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),其中a=2002/2003,b=2003/2002
先化简,再求值:(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),其中a=2002/2003,b=2003/2002

先化简,再求值:(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),其中a=2002/2003,b=2003/2002
原式=9a^2-12ab+4b^2-9a^2-3ab+2ab+4b^2
=8b^2-13ab

(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b)
=9a^2-4b^2-9a^2-3ab+2ab+4b^2
=-ab
因为a=2002/2003,b=2003/2002
所以原式=-1

ab=1
(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b),
=(9a^2-12ab+4b^2)-9a^2-3ab+2ab+4b^2
=-13ab+8b^2
=-13*1+8*(1003/2002)^8
=-13+8*2003^2/2002^2

(3a-2b)×(-2b+3a)-3a×(3a+b)+2b×(a+2b)
=9a^2+4b^2-12ab-9a^2-3ab+2ab+4b^2
=-13ab+8b^2